Теоретико-методологічні основи визначення дебіторської заборгованості та її класифікація - Чепець, Ольга Григорівна; Chepets, Olga; Юрченко, Сергій Васильович; Yurchenko, Serhii; Волчанська, Людмила Валентинівна; Volchanska, Lyudmila (Мукачівський державний університет, 2024)
В сучасних умовах для будь-якого підприємства, незважаючи на вид економічної діяльності та організаційно-правову форму господарювання, залишається досить актуальним питання обліку дебіторської заборгованості та її мінімізації. Саме від удосконалення управління дебіторської заборгованості залежить фінансовий стан підприємства, наявність оборотних коштів, розвиток підприємства. Метою статті є дослідження поняття дебіторської заборгованості, її класифікації, удосконалення обліку та визначення її впливу на фінансовий стан підприємства. У статті проаналізовано стан дебіторської заборгованості вітчизняних підприємств, досліджено особливості виникнення заборгованості, представлено класифікацію дебіторської заборгованості, яка дозволяє більш детально освідомити та зрозуміти різновиди об’єктів, дає можливість правильно побудувати облік дебіторської заборгованості на рахунках бухгалтерського обліку. Ефективне управління дебіторською заборгованістю дозволить у повному обсязі надати користувачам фінансової звітності достовірну облікову інформацію. Ретельний контроль за погашенням заборгованості дозволить значно знизити обсяги дебіторської заборгованості, збільшить оборотні активи, сприятиме активному розвитку та позитивно вплине на фінансовий стан підприємства. In modern conditions, for any enterprise, regardless of the type of economic activity and the organizational and legal form of management, the issue of accounting for receivables and its minimization remains quite relevant. The financial condition of the enterprise, the availability of working capital, and the development of the enterprise depend on the improvement of the management of receivables. The purpose of the article is to study the concept of accounts receivable, its classification, improvement of accounting and determination of its impact on the financial condition of the enterprise. The article analyzes the state of receivables of domestic enterprises, investigates the features of the occurrence of receivables, with the aim of optimizing the structure of receivables, presents the classification of receivables, which allows for a more detailed awareness and understanding of the types of objects, makes it possible to correctly build accounting for receivables on accounting accounts. On the basis of the formed classification of the conducted research of the regulatory and legislative framework and the study of scientific works of domestic scientists, the concept of "receivables" is defined. Measures to avoid the growth of receivables are proposed: it is necessary to use non-cash settlement based on a letter of credit to avoid the growth of receivables; in addition to the payment measure, it is necessary to implement an analysis of the customer's or buyer's solvency, carefully approach the conclusion of the contract with each individual customer, taking into account the conditions for late payment, conduct an inventory of payments with buyers in a timely manner, conduct thorough control over debt repayment, systematically analyze the turnover rate of receivables. Effective management of receivables will allow users of financial statements to be fully provided with reliable accounting information. Careful control over debt repayment will allow to significantly reduce the amount of receivables, increase current assets, promote active development and positively affect the financial condition of the enterprise.
Theoretical-methodological bases for determining receivables and their classification
Keywords: дебіторська заборгованість; receivables; класифікація дебіторської заборгованості; classification of receivables; управління дебіторською заборгованістю; management of receivables; фінансовий стан підприємства; financial condition of the enterprise